The relationship between population growth and economic growth in Egypt: A geographical perspective - Elmoughazi, Ahmed Fouad (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
The population is one of the most important factors of production, and its characteristics determine whether population growth is a blessing that enhances the state’s competitiveness or a burden that strains resources and the environment. There are five perspectives regarding the relationship between population growth and economic growth, which are: Population growth does not contribute to economic growth, Population growth stimulates economic growth, The population effect is neutral, interrelationship, and The relationship changes over time. In Egypt, the correlation between population growth and economic growth is highly significant; the first rate reflects the increase in the size of the population, while the other rate reflects the economic aspect, as well as the growing concern regarding the dangers of population increase on economic growth in Egypt. Purpose: The study intends to explore the correlation between population growth and economic growth in Egypt from 1993 to 2023, with a specific focus on the various governorates in 2023; Determining the impact of population growth on economic growth in Egypt during the period 1993-2023, And how have the rates of economic growth and population growth changed in Egypt, the optimal population size for Egypt, and the limits of the relationship between the annual population growth rate and the economic growth rate. Research methods: The study followed an objective and historical approach, in addition to descriptive and cartographic methods, as well as statistical methods. The data used in this study’s statistical analysis were obtained from the Egypt Demographic and Health Survey 2014 (EDHS), Egypt Family Health Survey 2021(EFHS), the Ministry of Planning, Economic Development, and International Cooperation, and CAPMAS 2017. Every governorate in Egypt is covered under the current study. Research results: The study revealed that the current population growth rate in Egypt is 1.90%, which requires an economic growth rate exceeding 5.7% annually for citizens to reap the benefits of development; however, the economic growth has not reached this level. The study revealed that there is a strong inverse correlation (-0.938*) between the population growth rate and the eco-nomic growth rate, especially Upper Egypt governorates are the most in need of care. Recommendations: It recommended the necessity of working on three pillars. The first is the population, through supporting the national strategy for population and development in Egypt (2023 - 2030) and controlling the population growth rate. The second is to work on increasing the economic growth rate, especially in the underprivileged governorates that suffer from a high population growth rate and a low economic growth rate, such as the Red Sea Governorate, Marsa Matrouh Governorate, Assiut Governorate, Minya Governorate, and Fayoum Governorate. The third is to work on integrating the economic dimension with the population dimension.